EVALUATION OF GROWTH OF EXPORTS OF AGRIBUSINESS IN RIO GRANDE DO SUL: AN APPLICATION OF THE METHOD CONSTANT-MARKET-SHARE - Fries, Carol Deitos; Coronel, Daniel Arruda; Vieira, Kelmara Mendes; Bender Filho, Reisoli (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The state of Rio Grande do Sul is considered one of the biggest producer and exporter of Brazilian products in agribusiness. Among the main product exports are: soy grain, meat and tobacco, in wich the main destination markets are the European Union, China and Russia. The aim of this work is to identify the sources of growth in these product exports through the model Constant Market Share (CMS). For this it was used data of exports in Rio Grande do Sul, global exports, European Union, China and Russia, soy grains, meat and tobacco in the period from 2001 to 2010. After that, the data were divided in three periods: 2001 to 2004 (period I), 2005 to 2007 (period II) and 2008 to 2010 (period III). The results indicated that the main source of growth for soy grains, comparing period II with period I was the growth of world trade, and the tobacco and the meat was the competitiveness, and period III with the period II was the growth of world trade for all products analyzed.